The main effect and gene-environment interaction effect of the ADCYAP1R1 polymorphism rs2267735 on the course of posttraumatic stress disorder symptoms—A longitudinal analysis - Zhang, Jingyi; Li, Gen; Yang, Haibo; Cao, Chengqi; Fang, Ruojiao; Liu, Ping; Luo, Shu; Zhao, Guangyi; Zhang, Yingqian; Zhang, Kunlin; Wang, Li (Frontiers in Psychiatry, 2022)
Background: Many studies have been performed to investigate the association between the ADCYAP1R1 polymorphism rs2267735 and posttraumatic stress disorder (PTSD), but the results have been inconsistent, and the way in which this gene affects the course of PTSD has not been widely investigated. Thus, a longitudinal study of the course (development trajectory) of PTSD is needed. Methods: In this study, we performed a longitudinal analysis of rs2267735 in 1017 young, trauma-exposed Chinese people (549 females and 468 males, ranging from 7 to 11 years old). At four time points after trauma exposure (2.5 years, 3.5 years, 4.5 years and 5.5 years), we measured PTSD symptoms with the University of California, Los Angeles PTSD Reaction Index (PTSD-RI) for DSM-IV (Child Version). We employed a latent growth model (LGM) for the longitudinal data to test the association between rs2267735 (main and gene-environment interaction effects) and the course of PTSD symptoms. Results: The results of LGM showed that the gene-environment interaction (rs2267735×trauma exposure) effects were associated with PTSD symptoms in girls at 2.5 years (β = -0.291 and P = 0.013 for LGM intercept). The gene-environment interaction (rs2267735×trauma exposure) effect was also correlated with PTSD symptoms in girls at 3.5 and 4.5 years (β = -0.264 and P = 0.005; β = -0.217 and P = 0.013). Conclusions: Our study revealed that the gene-environment interaction of the ADCYAP1R1 polymorphism rs2267735 is associated with PTSD symptoms in girls at 2.5 years and that the effects may be stable over time and not related to the PTSD symptom recovery rate. This is the first study to detect the how the ADCYAP1R1 gene affects the course of PTSD after trauma exposure in a longitudinal view.